The rise of facial palsy on social media over the last 5 years - Knoedler, Leonard; Knoedler, Samuel; Chartier, Christian; Panayi, Adriana C.; Orgill, Dennis P.; Moog, Philipp; Özdemir, Berkin; von Isenburg, Sarah; Studier-Fischer, Alexander; Prantl, Lukas; Kehrer, Andreas (The journal of craniofacial surgery, 2023)
Background: - Social media (SoMe) has become a powerful platform for distributing health information. Facial palsy (FP) results in functional and social impairment and lowers quality of life. Social media may help to raise awareness of FP sequalae. This study aims to determine the FP information growth on SoMe platforms and parameters that influence user engagement on FP content. - Methods: - Five commonly used SoMe platforms (Facebook, Instagram, TikTok, Twitter, and Reddit) were analyzed. Data on 18 FP hashtags and their social interaction parameters (posts, likes, reaches, comments, shares, language, and country of origin) over the past 5 years (July 31, 2016, to July 31, 2021) were collected. In-depth account analysis was performed on the 5 most popular Instagram profiles associated with FP. - Results: - The annual growth curve was positive on each platform. Facial Palsy Awareness Week 2021 trended best on TikTok. Facebook accumulated 315,411 likes and 1,922,678 reaches on 8356 posts. On Instagram, 24,968 posts gathered 4,904,124 likes and 9,215,852 reaches. TikTok users interacted on 3565 posts, accumulating 4,304,155 likes and 4,200,368 reaches. The implementation of reels (P<0.001) and the profile host interacting with their followers by liking (P<0.001) and replying (P<0.001) to users’ comments significantly increased the engagement rate. - Conclusions: - Facial palsy is of increasing interest on SoMe. Facial palsy surgeons may post reels, interact with their community, and engage into FPAW to promote user engagement.
Gesehen am 22.06.2023